2022
DOI: 10.1186/s13075-022-02799-6
|View full text |Cite
|
Sign up to set email alerts
|

High risk of depression, anxiety, and an unfavorable complex comorbidity profile is associated with SLE: a nationwide patient-level study

Abstract: Objectives The aim of this national population-based, retrospective database study is to compare the comorbidity profiles of systemic lupus erythematosus (SLE) patients and general population controls matched for age, gender, and region and assess the risk of depression or anxiety when controlled for age, gender and adjusted for the Charlson Comorbidity Index (CCI). Methods Claims data of 1051 patients diagnosed with SLE (full population between Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…SLE is prevalent in young women and often leads to multi-organ damage and flare-ups and remissions in SLE patients that can last for years or even decades. 51 , 52 Treatment of SLE primarily uses glucocorticoids and immunosuppressants; however, these drugs are known to cause many side effects. Researchers have tried to develop better treatment strategies based on findings from basic and clinical studies.…”
Section: Application Of Aav8 In Disease Treatmentmentioning
confidence: 99%
“…SLE is prevalent in young women and often leads to multi-organ damage and flare-ups and remissions in SLE patients that can last for years or even decades. 51 , 52 Treatment of SLE primarily uses glucocorticoids and immunosuppressants; however, these drugs are known to cause many side effects. Researchers have tried to develop better treatment strategies based on findings from basic and clinical studies.…”
Section: Application Of Aav8 In Disease Treatmentmentioning
confidence: 99%
“…Prior to the pandemic onset, people with SARD likely had a higher prevalence of stress-related disorders than those without SARD. [13][14][15][16][17][18] With the onset of the pandemic, patients with SARD taking immunosuppressants may have experienced more fear and anxiety than those in the general population due to the increased likelihood of severe illness tied to immunosuppression. 19,20 Reports from the initial COVID-19 outbreak in China and Italy suggested that patients with SARD experienced more severe PTSD symptoms early in the pandemic than did those without SARD.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…How the COVID‐19 pandemic added to the multifaceted relationship between rheumatic disease and PTSD is not understood. Prior to the pandemic onset, people with SARD likely had a higher prevalence of stress‐related disorders than those without SARD 13–18 . With the onset of the pandemic, patients with SARD taking immunosuppressants may have experienced more fear and anxiety than those in the general population due to the increased likelihood of severe illness tied to immunosuppression 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been proposed as contributing factors to the development of NPSLE symptoms, including the presence of inflammatory cytokines and autoantibodies, blood-brain barrier disruption, and cerebrovascular alterations; it has also been suggested that NPSLE could be attributed to the damage generated by the disease and the application of different treatments (Kósa et al, 2022; Liu et al, 2022; Sarwar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Pain, fatigue, cognitive dysfunction, major depression, and anxiety prevalence are estimated to be higher among people with SLE than in the general population. Depression and anxiety are considered among the most frequent and impactful neuropsychiatric manifestations of SLE; depression prevalence ranges between 2% and 91.7%, whereas anxiety is estimated to affect between 6.4% and 40% of the people with SLE (Kósa et al, 2022).…”
Section: Introductionmentioning
confidence: 99%